Workshop: Theory Development Within the Information Sciences. (February 2017) - Chu, Sam; Sonnenwald, Diane H.; Wu, Mei‐Mei; Chang, ShanJu Lin
Abstract : EDITOR'S SUMMARY The Theory Development within the Information Sciences workshop was held on October 15, 2016, at the ASIS&T Annual Meeting in Copenhagen, Denmark. The two main goals of the theory development workshop were to understand stages of theory development and discuss solutions to common challenges in the field, and to gauge the interests of the participants on theory development strategies. Diane Sonnenwald gave an overview on theory development based on her own experiences, Sam Chu talked about theory development applied to inquiry project‐based learning, Mei‐Mei Wu discussed multi methodologies in information retrieval and ShanJu Lin Chang touched on theory development processes in research on browsing phenomena. The workshop's second half was a roundtable discussion that involved participants discussing challenges in the field and receiving feedback from the presenters.